Dualisme Konsep Yom YHWH dalam Pengharapan Mesianik Nabi Zefanya - Gernaida Krisna R. Pakpahan (Badan Musyawarah Perguruan Tinggi Keagamaan Kristen Indonesia, 2022)
This article seeks to highlight the problem of the theological complexity of the prophet Zephaniah regarding the idea of yom YHWH, or